An Econometric Analysis of Residential Fuel Choice in Nigeria: Application of Access Framework (2023)
Despite global calls for a transition to modern energy, Nigerian households continue to face obstacles in accessing clean cooking energy. This paper examines the barriers to household fuel choice in rural and urban areas of Ogun Sate, Nigeria, employing an access framework. Through a cross-sectional study involving 597 households, we examined the factors associated with the selection of household cooking fuel and the access challenges. The framework conceptualises fuel choice as a function of three key access dimensions: affordability, availability, and acceptability, using multinomial logit regression. The findings showed that firewood and kerosene remain Nigeria’s dominant household fuel sources. The results highlight that fuel choice is influenced not only by affordability factors but also by factors related to availability and acceptability. Consequently, the study recommends a comprehensive approach beyond affordability, to ensure modern energy sources are culturally acceptable while establishing secure supply chains towards a more environmentally sustainable energy future.